The Impact of Noise in Industrial Work Environments A Field Study at Mellitah Oil & Gas - Karema Ramadan Zidan; Raniyah Almahdi Aboukhadeer (Libyan Journal of Medical and Applied Sciences, 2025)
This study investigates the impact of noise on workers in industrial work environments and evaluates the level of workers’ awareness of protective measures against noise. The research adopted a descriptive-analytical approach, utilizing data collected through a structured questionnaire covering two main axes: the health effects of noise and noise protection measures. The study focused on Mellitah Oil & Gas, with a randomly selected sample of 52 participants. The results indicated that a considerable proportion of workers (73.1%) were aware of the general health effects of noise. It was also found that noise has a significant impact on hearing (63.5%), contributes to elevated blood pressure (53.8%), and negatively affects concentration (57.7%), thereby increasing the likelihood of occupational accidents. Furthermore, the study revealed deficiencies in the monitoring of preventive health measures (42.3%). Regarding the second axis, the findings showed a clear shortcoming in awareness campaigns (46.2%) and workplace design (48.1%), while the availability of safety equipment was found to be moderately adequate (55.8%), The study recommends the establishment of a periodic medical screening system with strict adherence, strengthening training programs and awareness campaigns, and improving workplace conditions through effective monitoring and regular follow-up mechanisms.